(untitled) (Visnyk NTUU KPI Seriia - Radiotekhnika Radioaparatobuduvannia, 2011)
The application expedience and stages expert evaluation, the conditions of the expert method use, the composition of the expert commission requirements and the qualification of the expert criterions are considered. The definition of the concordance factor for the judgments experts’ concordance and the calculation for it are given. The Delphi method application in case the extent of the judgments experts’ concordance isn’t satisfactory is analyzed. The expert estimation methods of radio-electronic tools consumer properties at the life cycle different stages, depending on the method and the make an examination procedure (the direct dimension, the ranking, the comparison) are considered.